Carbon nanotubes accelerated growth by iron nanoparticles under microwave heating. Issue 12 (2nd December 2019) - Chen, Taiping; Liu, Huanpeng; Yang, Chenyu; Zhu, Miao; Li, Yang; Wang, Shaowei; Bie, Rushan
Abstract: In this paper, the rapid growth characteristics of CNTs synthesized by microwave (MW) heating of ferrocene and graphite powders under argon atmosphere were investigated. The SEM and TEM results show that most of the iron nanoparticle (NPs) catalysts exhibited aggregated morphology. Meanwhile, dense clusters of CNTs with the maximum length up to 30 μm are formed on the aggregation of Fe NPs under MW-irradiation 30 seconds, while from the dispersed Fe NPs in general are carbon nano-onions, short and fine CNTs. Therefore, the rapid growth of the CNTs is associated with the aggregated morphology and the subsequent coalescent process of iron NPs. It is speculated that the formation of the growth sites of CNTs provided on the Fe NPs during the coalescence of them is a crucial factor for the ultrafast growth of CNTs.